Oligomer β-amyloid Induces Hyperactivation of Ras to Impede NMDA Receptor-Dependent Long-Term Potentiation in Hippocampal CA1 of Mice - Wang, Ya; Shi, Zhaochun; Zhang, Yajie; Yan, Jun; Yu, Wenfeng; Chen, Ling (Frontiers in Pharmacology, 2020)
The activity of Ras, a small GTPase protein, is increased in brains with Alzheimer’s disease. The objective of this study was to determine the influence of oligomeric Aβ1-42 on the activation of Ras, and the involvement of the Ras hyperactivity in Aβ1-42-induced deficits in spatial cognition and hippocampal synaptic plasticity. Herein, we show that intracerebroventricular injection of Aβ1-42 in mice (Aβ-mice) enhanced hippocampal Ras activation and expression, while 60 min incubation of hippocampal slices in Aβ1-42 (Aβ-slices) only elevated Ras activity. Aβ-mice showed deficits in spatial cognition and NMDA receptor (NMDAR)-dependent long-term potentiation (LTP) in hippocampal CA1, but basal synaptic transmission was enhanced. The above effects of Aβ1-42 were corrected by the Ras inhibitor farnesylthiosalicylic acid (FTS). ERK2 phosphorylation increased, and Src phosphorylation decreased in Aβ-mice and Aβ1-42-slices. Both were corrected by FTS. In CA1 pyramidal cells of Aβ1-42-slices, the response of AMPA receptor and phosphorylation of GluR1 were enhanced with dependence on Ras activation rather than ERK signaling. In contrast, NMDA receptor (NMDAR) function and GluN2A/2B phosphorylation were downregulated in Aβ1-42-slices, which was recovered by application of FTS or the Src activator ouabain, and mimicked in control slices treated with the Src inhibitor PP2. The administration of PP2 impaired the spatial cognition and LTP induction in control mice and FTS-treated Aβ-mice. The treatment of Aβ-mice with ouabain rescued Aβ-impaired spatial cognition and LTP. Overall, the results indicate that the oligomeric Aβ1-42 hyperactivates Ras and thereby causes the downregulation of Src which impedes NMDAR-dependent LTP induction resulting in cognitive deficits.